2017
DOI: 10.4314/sajas.v47i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA damage in relation to lipid peroxidation following freezing-thawing of boar semen

Abstract: This study investigated the relationships between lipid peroxidation (LPO) and sperm DNA damage following freezing-thawing of boar semen in different extenders. The comet assay was used to measure the extent of sperm DNA damage in a cryoprotectant-free extender or in cryoprotectant-based extenders after single and repeated freezing and thawing. As well as an analysis of sperm motion characteristics, mitochondrial function, membrane integrity, and lipid peroxidation (LPO) were assessed simultaneously with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The viability values found in the thawed semen are similar to those reported by Roca et al (2006). Similar to the current results, decreased spermatozoa with intact acrosome after freezing-thawing have been reported by other authors (Trzcińska et al, 2015;Fraser et al, 2017). This damage was more evident in cells from ejaculates diluted with BTS compared with semen that was not diluted.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The viability values found in the thawed semen are similar to those reported by Roca et al (2006). Similar to the current results, decreased spermatozoa with intact acrosome after freezing-thawing have been reported by other authors (Trzcińska et al, 2015;Fraser et al, 2017). This damage was more evident in cells from ejaculates diluted with BTS compared with semen that was not diluted.…”
supporting
confidence: 92%
“…Freeze-thawed boar semen has limited commercial use because during the freezing-thawing process, 50% of the spermatozoa lose their fertilizing capacity (Qian et al, 2016) as a result of thermal shock, which compromises viability and integrity of DNA and increased lipid peroxidation of membrane phospholipids (Fraser et al, 2017). Cryodamage is not restricted to sperm membrane, but affects the integrity of sperm chromatin (nucleoprotein structure and DNA) and mitochondrial function, involves degradation of mRNAs, and impairs the function of certain proteins (Yeste, 2016).…”
mentioning
confidence: 99%
“…The different study has been shown that ROS level has a positive correlation with the reduction sperm parameters, DNA damage, DNA fragmentation and chromatin deficiency (Saeednia et al, 2015). Since DNA damage leads to sperm dysfunction and male infertility, it is necessary to evaluate sperm chromatin after the cryopreservation process (Fraser et al, 2017). The result of many study indicated that are significant relationship between reduced amount antioxidants and low quality of sperm parameters and male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Cryo-induced damage to spermatozoa is attributed to membrane deterioration caused mainly by the formation of intracellular ice and increased oxidative stress, resulting in a loss of the sperm fertilizing ability. 3 It is noteworthy that ageing-dependent processes in frozen-thawed semen occur in different sperm compartments, and are associated with membrane modifications of specific lipid-protein interactions, activation of an apoptosis-like mechanism and reduced genomic integrity, which consequently compromise sperm cryo-survival. 4,5 Moreover, ageing is a natural process occurring in sperm cells during semen preservation, and there is no single sperm test that can effectively predict the fertilizing capacity of semen following the different reproductive technologies.…”
mentioning
confidence: 99%